2001
DOI: 10.1093/ije/30.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis and associated factors in areas of high levels of poverty in Chiapas, Mexico

Abstract: The high prevalence of PTB detected indicates the need, both in the area studied and in others with similar conditions, to develop PTB control programmes which give priority to early diagnosis and to the provision of adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
3
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
1
16
3
4
Order By: Relevance
“…However, there were only 18 cases; the study had very low power to detect any such potential association of interest. Aside from cough of 2 or more weeks duration, which is incorporated within our algorithm, among the other symptoms considered, none was significantly associated with pulmonary tuberculosis status, which is in contrast to the finding of a study in Mexico [19], wherein blood in sputum was significant predictor of pulmonary tuberculosis. This clinical variable was not statistically significant in our study perhaps due to the low power and may merit further evaluation.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…However, there were only 18 cases; the study had very low power to detect any such potential association of interest. Aside from cough of 2 or more weeks duration, which is incorporated within our algorithm, among the other symptoms considered, none was significantly associated with pulmonary tuberculosis status, which is in contrast to the finding of a study in Mexico [19], wherein blood in sputum was significant predictor of pulmonary tuberculosis. This clinical variable was not statistically significant in our study perhaps due to the low power and may merit further evaluation.…”
Section: Discussioncontrasting
confidence: 95%
“…Alvi et al [17] used a rapid village survey method, which entailed going to every house [18], almost comparable with the sampling design used in this study. Prevalence of pulmonary tuberculosis among those who provided at least one sputum sample was 16.2%, which is twice as high as reported in marginalized communities in Mexico [19]. The factors which possibly could explain this difference may include differing government spending priorities for public health, rates of case detection, and the subsequent treatment of cases which may have reduced the rates of secondary transmission in their settings.…”
Section: Discussionmentioning
confidence: 97%
“…The results found are in agreement with other studies of populations marginalized in socioeconomic terms and in access to health services, carried out not only in Ecuador 3 but also in México, 16 and in which the patchwork methodology was also used.…”
Section: Discussionsupporting
confidence: 91%
“…Because there were significant socioeconomic differences noted between diabetic and nondiabetic patients, it is possible that persons with better access to health care services were more likely to be diagnosed with both diabetes and tuberculosis. However, in this study, patients with tuberculosis were actively sought, and prior analysis has shown tuberculosis to be more commonly diagnosed in individuals of lower socioeconomic status (27). Therefore, there was no differential opportunity for diagnosis of tuberculosis according to availability of health services.…”
Section: Figure 1-impact Of Undersampling and Increase In Interval Bementioning
confidence: 95%